Development of PBL Modul-El to Improve Problem Solving Students of Physics Education Program - Ragil Saputri; Insih Wilujeng; Jumadi Jumadi; Sabar Nurohman; Aditya Yoga Purnama (Postgraduate, University of Mataram, 2023)
Electronic modules are teaching materials that are systematically arranged to achieve learning objectives in electronic form with which includes writing, animation, video, and navigation that makes learning more interesting, interactive, active, and motivating which can facilitate students' problem solving skills. This study aims to see whether there is an increase in students' problem solving skills after using PBL-based el-modules. The method in this research is research and development, which is a research method used to produce and test the feasibility of certain products. The subjects of this study were second semester students who were taking basic physics courses. This research was conducted at the Physics Education Study Program of Sarjanawiyata Tamansiswa University with the subject matter of